Pengaruh Penambahan Rumput Laut (Eucheuma Cottoni) Terhadap Sifat Organoleptik Dan Daya Terima Chiffon Cake Maco Pada Remaja Obesitas - Indah Puji Rahmani; Igde Narda Widiada; Made Darawati; Iketut Swirya Jaya (Poltekkes Kemenkes Mataram, 2019)
The purpose of this study is to determine the effect of adding seaweed to the organoleptic test and the acceptance of maco cake chiffon in obese adolescents. This study used a Completely Randomized Design (CRD), with 5 treatments of adding seaweed consisting of t1 (10%), t2 (20%), t3 (30%), t4 (40%), t5 (50%). The results showed that t2 (20%) was the most preferred sample of panelists, the results of analyzing food fiber in the most preferred products were 13.64%, product acceptance was good at 24 people (80%) and marketing of maco cake chiffon in the category loss.